2015 IEEE International Conference on Electronics, Circuits, and Systems (ICECS) 2015
DOI: 10.1109/icecs.2015.7440259
|View full text |Cite
|
Sign up to set email alerts
|

Compact highly selective passive notch filter for 3.1–5 GHz UWB receiver system

Abstract: This paper deals with the design of highly selective passive notch filter working at 2.4 GHz for 3.1-5 GHz UWB receiver system. The proposed filter aims to enable IEEE 802.11 b/g and UWB standard coexistence in the same terminal device. The filter topology is composed of two paths: the first path contains an all-pass function while the second path contains a band-pass one. By this way, the signal is divided at the circuit input and is combined at its output forming a notch response that exhibits a high rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Larger values of µ were investigated and found to reduce losses and increase the passband of the bandpass channel and the notch depth. Stopband rejection can be greatly improved by fine-tuning 𝜆 according to Equation (21). For parameters in Table 1, the value of 𝜆 required for infinite rejection is 0.79, well within range for the coupling tuning mechanism.…”
Section: Single-notch Filtermentioning
confidence: 77%
See 3 more Smart Citations
“…Larger values of µ were investigated and found to reduce losses and increase the passband of the bandpass channel and the notch depth. Stopband rejection can be greatly improved by fine-tuning 𝜆 according to Equation (21). For parameters in Table 1, the value of 𝜆 required for infinite rejection is 0.79, well within range for the coupling tuning mechanism.…”
Section: Single-notch Filtermentioning
confidence: 77%
“…Figure 4b shows the frequency dependence of scattering parameters for filters with lossy MI (1) and resistive narrowband (2) terminations for κ = 0.6, κ c = 0.3, Q = 200, and λ = 0.8746 from Equation (21). Both cases demonstrate excellent directional filtering with reflectance mostly <−30 dB within the passband, as well as infinite rejection at resonance.…”
Section: Infinite Rejectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [18], it was demonstrated that a highly selective bandstop filter response can be obtained at a fixed frequency f 0 when a bandpass branch designed at f 0 is combined to a PS branch that acts as a bypass signal inverter network. In an ideal case, the output signal is cancelled at this frequency when the signals propagating through the two branches are combined at the output with the same amplitudes but with 180° of phase difference.…”
Section: Structure Topology and Analysismentioning
confidence: 99%